Genetic diversity, asexual reproduction and conservation of the edible fruit tree Spondias purpurea L. (Anacardiaceae) in the Costa Rican tropical dry forest. - E Jacob Cristóbal-Pérez; Eric J Fuchs; Jorge Lobo; Mauricio Quesada (PLoS ONE, 2022)
The term circa situm has been used to describe different conservation strategies within agricultural landscapes. Circa situm conserves planted or remnant species in farmlands, where natural vegetation has been modified through anthropogenic intervention. It has been proposed that trees planted or retained under circa situm conditions may contribute to maintaining genetic diversity, however information on the role of this strategy in preserving genetic diversity is scarce. The aim of this study was to determine the levels of genetic diversity and structure, and mating patterns in planted and unmanaged stands of the tropical fruit tree Spondias purpurea L. in north western Costa Rica. In three localities, we used seven polymorphic microsatellite loci and genotyped 201 adults and 648 seeds from planted and wild stands. We found no differences in genetic diversity among planted and wild stands. Genetic structure analysis revealed that gene flow occurs among planted and wild stands within localities. Clones were present and their diversity and evenness were both high and similar between planted and wild stands. The number of pollen donors per progeny array was low (Nep = 1.01) which resulted in high levels of correlated paternity (rp = 0.9). Asexual seeds were found in 4.6% of the progeny arrays, which had multilocus genotypes that were identical to the maternal trees. Our results show that although planted stands under circa situm conditions can maintain similar levels of genetic diversity than wild stands, the low number of sires and asexual seed formation could threaten the long term persistence of populations.